The role of environmental filtering, geographic distance and dispersal barriers in shaping the turnover of plant and animal species in Amazonia - Cristian Dambros; Gabriela Zuquim; Gabriel M. Moulatlet; Flavia R. C. Costa; Hanna Tuomisto; Camila C. Ribas; Renato Azevedo; Fabricio Baccaro; Paulo E. D. Bobrowiec; Murilo S. Dias; Thaise Emilio; Helder M. V. Espirito-Santo; et al. (SPRINGER, 2022)
To determine the effect of rivers, environmental conditions, and isolation by distance on the distribution of species in Amazonia. Location: Brazilian Amazonia. Time period: Current. Major taxa studied: Birds, fishes, bats, ants, termites, butterflies, ferns + lycophytes, gingers and palms. We compiled a unique dataset of biotic and abiotic information from 822 plots spread over the Brazilian Amazon. We evaluated the effects of environment, geographic distance and dispersal barriers (rivers) on assemblage composition of animal and plant taxa using multivariate techniques and distance- and raw-data-based regression approaches. Environmental variables (soil/water), geographic distance, and rivers were associated with the distribution of most taxa. The wide and relatively old Amazon River tended to determine differences in community composition for most biological groups. Despite this association, environment and geographic distance were generally more important than rivers in explaining the changes in species composition. The results from multi-taxa comparisons suggest that variation in community composition in Amazonia reflects both dispersal limitation (isolation by distance or by large rivers) and the adaptation of species to local environmental conditions. Larger and older river barriers influenced the distribution of species. However, in general this effect is weaker than the effects of environmental gradients or geographical distance at broad scales in Amazonia, but the relative importance of each of these processes varies among biological groups.